Artistic education as a catalyst for interdisciplinary learning: stimulating creativity and critical thinking - Lucero Garcés, Marco Fabián; Torrel, Isabel Cristina; Montejo Rodríguez , Erley (Arandu UTIC, 2025)
This research focuses on artistic education as a catalyst for interdisciplinary learning at the Pedro Fermín Cevallos Educational Unit located in Ecuador. The main objective is to propose a pedagogical approach based on artistic education that contributes to the development of interdisciplinary learning among high school students. The methodology employed is framed within a qualitative approach, utilizing a descriptive-explanatory design. Non-participant observations were conducted in classrooms, structured surveys were administered to teachers and students, and semi-structured interviews were held with education experts. Data triangulation provided a comprehensive view of the current state of interdisciplinary learning and artistic education in the curriculum. Among the findings, a limited integration of artistic education within the curriculum was identified, which affects the development of key competencies such as creativity and critical thinking. Emerging pedagogical practices were observed that reflect the interest of some teachers in connecting the arts with other disciplines, although these are sporadic. The research culminated in a pedagogical proposal aimed at integrating artistic education into the high school curriculum, fostering an interdisciplinary approach that enriches learning and develops social and emotional skills in students.